O osobliwości pewnych niegładkich konstrukcji powierzchniowych (II) - Frąckiewicz, H.; Legat, A. (Engineering Transactions, 1968)
Making use of the static singularity criterion derived in Ref. [4] relations are obtained between the geometrical parameters of the structure. The satisfaction of these relations makes a structure singular that is behaving as a mechanism under the action of certain loads. The paper is concerned, in principle, with axially symmetric angular shells with more than one angular point of the longeron. In the limit case, however, the relations obtained are also valid for conical shells. For a few of the structure types analysed diagrams of dimensions of singular structures are plotted.